POLA KOMUNIKASI NONVERBAL PENYANDANG TUNARUNGU DI SUNGAI GUNTUNG, KECAMATAN KATEMAN, KABUPATEN INDRAGRI HILIR - Faizal Muhardiansah; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Deaf are those who experience interference with their sense of hearing, so that hearing is very low even at all can not hear what is being said or what was told to him. Deaf people use nonverbal language in communication. The pattern of nonverbal communication of the deaf and the people in the guntung river in Kateman subdistrict, Indragiri, downstream in the process of interaction is expected to be able to change the mindset of deaf people and be able to interpret messages well. This study aims to look at the kinesik, proxemic and paralinguistic messages of deaf people in the process of interacting in the guntung river community.This study uses a descriptive method with a qualitative approach. Informants in this study were 4 deaf people selected using a purposive technique. Data collection techniques in this study used in-depth observation, interview and documentation. This study uses interactive data analysis techniques that include three stages, namely data reduction, data presentation and conclusion.The results of this study are nonverbal communication patterns of people with hearing impairments using several nonverbal messages consisting of kinesik messages, proxemic messages and paralinguistic messages that can support the narrating process. Kinesik messages consist of facial expressions, deaf people use body parts to communicate and body language such as saying